Parameter identification for vertical ground reaction forces on feet while running. Issue 4 (December 2015) - Khajah, Tahsin; Hou, Gene
Abstract The human foot is subjected to ground reaction forces during running. These forces have been studied for decades to reduce the related injuries and increase comfort. A four-degree-of-freedom system has been used in the literature to simulate the human body motion during the touch-down. However, there are still inconsistencies between the simulation results and experimental measurements. In this study, an optimization technique is proposed to obtain the required parameters to estimate the vertical ground reaction force using the measurements from actual runners. The touch-down velocities of the rigid and wobbling body masses were also treated as optimization variables. It was shown that the proposed parameters can be adjusted to represent a particular shoe type. Specifically, vertical ground reaction force parameters and touch-down velocities were obtained for shoes with various insole properties and cushioning technologies. The results of this study suggest that the human locomotion system reacts to the shoe properties by regulating the velocities of the body wobbling and rigid masses. The magnitude and the load rate obtained using the proposed parameters are consistent with the experimental data. It is shown that the viscoelastic properties of the shoe will significantly affect the load rate but not the load magnitude.